Exploring of Parental Attitudes in the Context of the Digitalized Family - Durualp, Enver; Gunes, Lugen Ceren; Durualp, Ender; Durualp, Enver (Nesibe Aydin Education Inst, 2023)
The present descriptive survey research attempted to explore parents' digital parenting attitudes by certain variables related to children's use of technological tools. A total of 388 parents, 273 mothers and 115 fathers, with children aged 6-15 years were recruited for the study. The data were collected via Google forms using a demographic information form and the Digital Parenting Attitude Scale developed by Inan Kaya et al. and analyzed utilizing Mann-Whitney U and Kruskal-Wallis H tests. The findings revealed that the parents with children aged 11-15 years, with children using technological devices for 8 hours or more, and not supervising or restricting their children in the use of technological tools had a significantly stronger approval attitude toward the effective use of digital media. It was also found that parents with children watching TV the most, thinking that their children excessively use technological tools, and always supervising and restricting their children had a significantly stronger protective attitude against the risks of digital media. Overall, based on the findings, the paper concluded with some recommendations for parents, experts, and researchers.
Keywords: Digital Parenting; Digital Parenting Attitudes; Effective Use; Risk Protection; Technological Tools